Multiple threading of a triple-calix[6]arene host - Iuliano, Veronica; Ciao, Roberta; Vignola, Emanuele; Talotta, Carmen; Iannece, Patrizia; De Rosa, Margherita; Soriente, Annunziata; Gaeta, Carmine; Neri, Placido (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of the triple-calix[6]arene derivative 6 in which three calix[6]arene macrocycles are linked to a central 1,3,5-trimethylbenzene moiety is reported. Derivative 6 is able to give multiple-threading processes in the presence of dialkylammonium axles. The formation of pseudo[2]rotaxane, pseudo[3]rotaxane, and pseudo[4]rotaxane by threading one, two, and three, respectively, calix-wheels of 6 has been studied by 1D and 2D NMR, DOSY, and ESI-FT-ICR MS/MS experiments. The use of a directional alkylbenzylammonium axle led to the stereoselective formation of endo-alkyl pseudo[n]rotaxane stereoisomers.
Keywords: calixarene; multiple-threading; pseudo[n]rotaxane; stereoisomers

Encylopedia of Supramolecular Chemistry - Swiegers, G. F. (Self-Assembly: Terminology, 2004)

(untitled) - Yao, X.; Wang, X.; Jiang, T.; Ma, X.; Tian, H. (Langmuir, 2015)

(untitled) - Yao, X.; Li, T.; Wang, S.; Ma, X.; Tian, H. (Chem. Commun., 2014)

(untitled) - Yao, X.; Ma, X.; Tian, H. (J. Mater. Chem. C, 2019)

The Nature of the Mechanical Bond: From Molecules to Machines - Bruns, C. J.; Stoddart, J. F. (John Wiley & Sons, 2017)

(untitled) - Feringa, B. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Sauvage, J.-P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Stoddart, J. F. (Angew. Chem., Int. Ed., 2017)

Molecular Catenanes, Rotaxanes and Knots: A Journey Through the World of Molecular Topology - Sauvage, J.-P.; Dietrich-Buchecker, C. (Wiley-VCH, 1999)

(untitled) - Ashton, P. R.; Reder, A. S.; Spencer, N.; Stoddart, J. F. (J. Am. Chem. Soc., 1993)

(untitled) - Weidmann, J.-L.; Kern, J.-M.; Sauvage, J.-P.; Muscat, D.; Mullins, S.; Köhler, W.; Rosenauer, C.; Räder, H. J.; Martin, K.; Geerts, Y. (Chem. – Eur. J., 1999)

(untitled) - Li, Z.-T.; Becher, J. (Chem. Commun., 1996)

(untitled) - Frey, J.; Kraus, T.; Heitz, V.; Sauvage, J.-P. (Chem. Commun., 2005)

(untitled) - Frey, J.; Kraus, T.; Heitz, V.; Sauvage, J.-P. (Chem. – Eur. J., 2007)

(untitled) - Evans, N. H.; Serpell, C. J.; Beer, P. D. (Angew. Chem., Int. Ed., 2011)

(untitled) - Yang, L.; Langer, P.; Davies, E. S.; Baldoni, M.; Wickham, K.; Besley, N. A.; Besley, E.; Champness, N. R. (Chem. Sci., 2019)

(untitled) - Gaeta, C.; Troisi, F.; Neri, P. (Org. Lett., 2010)

(untitled) - Gaeta, C.; Talotta, C.; Margarucci, L.; Casapullo, A.; Neri, P. (J. Org. Chem., 2013)

(untitled) - Talotta, C.; De Simone, N. A.; Gaeta, C.; Neri, P. (Org. Lett., 2015)

(untitled) - Gaeta, C.; Talotta, C.; Farina, F.; Campi, G.; Camalli, M.; Neri, P. (Chem. – Eur. J., 2012)

(untitled) - Gaeta, C.; Talotta, C.; Farina, F.; Teixeira, F. A.; Marcos, P. M.; Ascenso, J. R.; Neri, P. (J. Org. Chem., 2012)

(untitled) - Talotta, C.; Gaeta, C.; De Rosa, M.; Ascenso, J. R.; Marcos, P. M.; Neri, P. (Eur. J. Org. Chem., 2016)

(untitled) - Pierro, T.; Gaeta, C.; Talotta, C.; Casapullo, A.; Neri, P. (Org. Lett., 2011)

(untitled) - Talotta, C.; Gaeta, C.; Neri, P. (Org. Lett., 2012)

(untitled) - Gaeta, C.; Talotta, C.; Mirra, S.; Margarucci, L.; Casapullo, A.; Neri, P. (Org. Lett., 2013)

Calixarenes and Beyond - Gaeta, C.; Talotta, C.; De Rosa, M.; Soriente, A.; Neri, P. (Springer, 2016)

(untitled) - Ciao, R.; Talotta, C.; Gaeta, C.; Margarucci, L.; Casapullo, A.; Neri, P. (Org. Lett., 2013)

(untitled) - Ciao, R.; Talotta, C.; Gaeta, C.; Neri, P. (Supramol. Chem., 2014)

(untitled) - de Mendoza, J.; Carramolino, M.; Cuevas, F.; Nieto, P. M.; Prados, P.; Reinhoudt, D. N.; Verboom, W.; Ungaro, R.; Casnati, A. (Synthesis, 1994)

(untitled) - De Rosa, M.; Soriente, A.; Concilio, G.; Talotta, C.; Gaeta, C.; Neri, P. (J. Org. Chem., 2015)

Calixarenes and Beyond - Arduini, A.; Orlandini, G.; Secchi, A.; Credi, A.; Silvi, S.; Venturi, M. (Springer, 2016)

(untitled) - Arduini, A.; Bussolati, R.; Credi, A.; Secchi, A.; Silvi, S.; Semeraro, M.; Venturi, M. (J. Am. Chem. Soc., 2013)

(untitled) - Arduini, A.; Calzavacca, F.; Pochini, A.; Secchi, A. (Chem. – Eur. J., 2003)

(untitled) - Arduini, A.; Ciesa, F.; Fragassi, M.; Pochini, A.; Secchi, A. (Angew. Chem., Int. Ed., 2005)

(untitled) - Arduini, A.; Credi, A.; Faimani, G.; Massera, C.; Pochini, A.; Secchi, A.; Semeraro, M.; Silvi, S.; Ugozzoli, F. (Chem. – Eur. J., 2008)

(untitled) - Arduini, A.; Bussolati, R.; Credi, A.; Monaco, S.; Secchi, A.; Silvi, S.; Venturi, M. (Chem. – Eur. J., 2012)

(untitled) - Zanichelli, V.; Ragazzon, G.; Arduini, A.; Credi, A.; Franchi, P.; Orlandini, G.; Venturi, M.; Lucarini, M.; Secchi, A.; Silvi, S. (Eur. J. Org. Chem., 2016)

(untitled) - La Manna, P.; Talotta, C.; Gaeta, C.; Soriente, A.; De Rosa, M.; Neri, P. (J. Org. Chem., 2017)

(untitled) - Talotta, C.; Gaeta, C.; Qi, Z.; Schalley, C. A.; Neri, P. (Angew. Chem., Int. Ed., 2013)